The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.bar.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audit committee characteristics on intellectual capital disclosure

Abstract: This paper, using data from 100 UK listed firms, investigates the relationship between audit committee characteristics and intellectual capital (IC) disclosure. We find that IC disclosure is positively associated with audit committee characteristics of size and frequency of meetings, and negatively associated with audit committee directors' shareholding. We find no significant relationship between IC disclosure and audit committee independence and financial expertise. We also observe variations in the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

54
428
10
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(508 citation statements)
references
References 66 publications
(174 reference statements)
54
428
10
16
Order By: Relevance
“…Therefore, the AC is viewed as a monitoring mechanism intended to reduce information asymmetries between management and stakeholders, since its key functions are to improve the quality and accuracy of financial information through constantly monitoring the management's opportunistic behaviours (e.g., Klein, 2002;Davidson et al, 2005;Pucheta-Martinez and Fuentes, 2007;. Dhaliwal et al, 2010;Li et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the AC is viewed as a monitoring mechanism intended to reduce information asymmetries between management and stakeholders, since its key functions are to improve the quality and accuracy of financial information through constantly monitoring the management's opportunistic behaviours (e.g., Klein, 2002;Davidson et al, 2005;Pucheta-Martinez and Fuentes, 2007;. Dhaliwal et al, 2010;Li et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature on AC has suggested that AC effectiveness essentially functions on AC characteristics (e. g. Persons, 2009;Bédard and Gendron, 2010;Dhaliwal et al, 2010;Li et al, 2012). Therefore, the perfect AC size with the right combination of skills and experience are critical in supporting the AC's ability in detecting and preventing earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakteritik corporate governance terutama komite audit diyakini dapat mempengaruhi luas lingkup integrated reporting. Riset yang menginvestigasi pengaruh karakteristik perusahaan misalnya komite audit terhadap integrated reporting diyakini penting karena komite audit seringkali dihubungkan dengan kualitas pelaporan keuangan (Bédard & Gendron, 2010;Li, Mangena, & Pike, 2012;Lisic, Neal, Zhang, & Zhang, 2015). Komite audit harus berperan aktif dalam mereview laporan keuangan termasuk integrated reporting dan harus memperhatikan semua aspek yang mungkin berdampak pada integritas integrated reporting (Ahmed Haji, 2015).…”
unclassified
“…Komite Audit adalah komite pengawas di bawah dewan komisaris karena dewan komisaris dalam menjalankan tugasnya melimpahkan tanggung jawab dalam proses pelaporan perusahaan kepada komite audit (Bédard & Gendron, 2010;Ghafran & O'Sullivan, 2013;Li et al, 2012). Komite audit diyakini memiliki peran dalam mengurangi asimetri informasi (Akhtaruddin & Haron, 2010;Al Daoud, Ku Ismail, & Lode, 2015) dan akibatnya mengurangi biaya agensi (Bédard & Gendron, 2010).…”
unclassified